2014
DOI: 10.1021/am405509t
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Photopolymer Linear Variable Filter with Enhanced Blue Reflection

Abstract: A single beam one-step holographic interferometry method was developed to fabricate porous polymer structures with controllable pore size and location to produce compact graded photonic bandgap structures for linear variable optical filters. This technology is based on holographic polymer dispersed liquid crystal materials. By introducing a forced internal reflection, the optical reflection throughout the visible spectral region, from blue to red, is high and uniform. In addition, the control of the bandwidth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Laser interference is a simple and widely used method for the fabrication of large-area and non-defect structures, which paves the way for the wide application of these periodic structures [66][67][68][69].…”
Section: Structures For Optical Manipulationmentioning
confidence: 99%
“…Laser interference is a simple and widely used method for the fabrication of large-area and non-defect structures, which paves the way for the wide application of these periodic structures [66][67][68][69].…”
Section: Structures For Optical Manipulationmentioning
confidence: 99%
“…For example, Cartwright et al reported a graded reflection grating based on the H-PDLC material system [43,44]. An obvious rainbow-colored reflection was observed from the same viewing angle by a modification to this standard configuration where the triangular prism is replaced with a cylindrical lens.…”
Section: Holographic Polymer-dispersed Lcmentioning
confidence: 99%
“…1517 Our previously reported spatially graded polymeric PhC structure is an example. 1820 For a given porous material, however, pore size distributions cannot be easily tailored or intentionally modified, especially postpreparation. This is due to low Young’s moduli and thermal expansion coefficients of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials are also established as optical elements for colorimetric humidity and/or chemical sensors. For instance, micro-/nanoporous photonic crystals (PhCs) have been developed using self-assembly and holographic lithography methods to spatially tune the distribution of polymer-rich (P-rich) and void-rich (V-rich) regions within subwavelength dimensions. Therefore, the created photonic bandgaps can result in controlled reflection at selected wavelengths. Our previously reported spatially graded polymeric PhC structure is an example. For a given porous material, however, pore size distributions cannot be easily tailored or intentionally modified, especially postpreparation. This is due to low Young’s moduli and thermal expansion coefficients of the materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation